An exploratory study of the evolution of urban green spaces in Lisbon using diachronic analysis of orthophoto maps - Ramneantu, Krisztina; Marat-Mendes, Teresa (Journal of Architecture and Urbanism, 2024)
Green urbanism, namely in the form of consolidated urban green spaces (UGSs), has gained traction along with the reformist impetus of urban design, based on the ideal of efficient, functional, sustainable cities that promote a better quality of life for their citizens and on the notion of making urban expansion compatible with natural resources. Using a diachronic analysis (1995–2020) of the orthophoto maps of 38 UGSs included in the last version of the main municipality’s legislation, framed within the Plano Director Municipal (PDM), whose first version was approved in 1994, we assessed the situation and evolution of the UGSs in the centre of Lisbon, Portugal. We conclude that with fewer or more incidences, depending on the periods analysed, the structure of UGSs in the centre of Lisbon has undergone significant changes, whether in terms of the implementation and requalification of existing UGSs or in terms of the increment and quality of UGSs (space created), thus respecting to a lesser or greater degree the strategic lines defined in various plans, as is the case of the PDM itself, but also of other important documents, such as the Carta Estratégica 2010–2024, Estratégia de Reabilitação Urbana 2011–2024 and Estratégia Regional de Lisboa 2030.